Butterflies (Lepidoptera: Papilionoidea) deposited in the Gregório Bondar Entomological Collection of the Cocoa Research Center, Ilhéus, Bahia, Brazil - Gabriel Vila-Verde; Clemensou Reis; Márlon Paluch; Jacques Hubert Charles Delabie (EntomoBrasilis)
The Gregório Bondar Entomological Collection (CEGB) of the Cocoa Research Center (CEPEC) has its origins in the 1930s with Dr. Gregório Bondar's insect collection that he constituted in the state of Bahia, Brazil. Bondar, a Russian-Brazilian entomologist, significantly contributed to Brazilian entomology and agriculture, and his extensive collection was in great part donated to the American Museum of Natural History. A smaller portion remained in Brazil and was eventually transferred to CEPEC in the 1960s. The collection, originally known as "Entomoteca Gregório Bondar", has grown to over 30,000 specimens by the 1980s. It holds valuable historical data that supports biodiversity monitoring and ecological research. The CEGB's Lepidoptera section features specimens collected from 1936 to 2024, mostly from the Atlantic Forest biome. This article aims to contribute to the knowledge of the distribution of butterflies in the Atlantic Forest, primarily from southern Bahia, by providing data on the specimens deposited in the CEGB at CEPEC in Ilhéus, Bahia, Brazil. A total of 531 specimens in 249 species of butterflies distributed within six families were recorded: 282 Nymphalidae (109 spp.), 107 Hesperiidae (63 spp.), 60 Riodinidae (31 spp.), 46 Lycaenidae (30 spp.), 33 Pieridae (14 spp.), and three Papilionidae (2 spp.). Specimens were collected from 11 localities in the Atlantic Forest biome. The CEGB provides data on butterfly distribution, including new records for the state of Bahia and the Atlantic Forest, highlighting its significance for research and conservation efforts.